The Influence of Leadership Style, Motivation, and Compensation on Employee Performance of PT. Pos Logistics Indonesia - Junaidi , Achmad; Nindita, Yoga; Gunawan, Cecep (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to analyze the influence of leadership style, motivation, and compensation on employee performance of PT. Pos Logistics Indonesia. The method used in this study is an explanatory method, by taking a sample from all employees of PT. Pos Logistics Indonesia. This research uses primary data and secondary data. The data analysis method used in this study is Multiple Linear Regression with Ordinary Least Square (OLS) using SPSS 17 Software. The results showed that the leadership style variables has a positive and significant effect on employee performance with a coefficient of 0.270 which means that when the leadership style rises by one unit, the employee's performance will increase by 0.270. Motivation variables have positive and significant effect on employee performance with coefficient of 0.569, which means that when motivation increases by one unit, employee performance will increase by 0.569. Compensation variable has a positive and significant effect on employee performance with a coefficient of 0, 261 which means that when compensation increases by one unit, employee performance will increase by 0.261. While simultaneously the leadership style, motivation, and compensation are positively and significantly effect on employees performance of PT. Pos Logistics Indonesia.